Evaluasi dan Perbaikan Desain Antarmuka Pengguna pada Website Polresta Malang dengan Metode Human Centered Design (HCD) - Ella Inayatul Khusna; Satrio Hadi Wijoyo; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Polres kota Malang website has functions as a media to provide an information about news and society service for local society in Malang city. Polres kota Malang website is managed by humas department which has three division. This study aims to improve the user interface design and increase usability value of Polres kota Malang website. Human Centered Design (HCD) method used to making design improvements and it has several stages, determining the context or situation of the user, determining user requirements, making improvement designs and evaluating designs that have been made. In evaluating usability, the method used is Website Usability Evaluation Tool (WEBUSE). The results of prototype design solutions is Increasing usability levels that were previously good to excellent. The value of Usability in the Content category, Organization & Readability and Performance & Effectiveness has an increase 0,16. Navigation & Link and User Interface Design category has an increase 0,19.